Christ Witnessing to Culture: Toward a New Paradigm between Christ and Culture - Allbee, Rick (Stone-Campbell journal, 2005)
This article proposes a new paradigm for the relationship between Christ and culture that interacts with H. Richard Niebuhrs well-known five paradigms. Attempting to draw upon the strengths of his proposals, the proposal being put forward here, Christ witnessing to Culture, is a paradigm grounded in fundamental, biblical doctrine, has a christological basis, reflects the practice of the early church, and facilitates personal evangelism as well as Christian cultural witness. It is therefore recommended over Niebuhrs paradigms whose strengths it incorporates while simultaneously rejecting their weaknesses.